2017
DOI: 10.1093/ajh/hpx117
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to LPS Alters The Intrarenal RAS in Offspring, Which Is Ameliorated by Adipose Tissue-Derived Mesenchymal Stem Cells

Abstract: Prenatal exposure to LPS activates the intrarenal RAS but not the circulating RAS and thus induces increases in blood pressure in adult offspring; however, ADSCs treatment attenuates the blood pressure increases resulting from LPS exposure and also ameliorates the other phenotypic changes induced by LPS treatment by inhibiting intrarenal RAS activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…IHC staining of CRC tissue samples and xenografted tumors was performed as described previously [40]. Sections were incubated with primary antibody PHLDA2 (Bs-6884R; 1:100), KI67 (ab15580; 1:200).…”
Section: Immunohistochemistry (Ihc) and Immunofluorescence (If)mentioning
confidence: 99%
“…IHC staining of CRC tissue samples and xenografted tumors was performed as described previously [40]. Sections were incubated with primary antibody PHLDA2 (Bs-6884R; 1:100), KI67 (ab15580; 1:200).…”
Section: Immunohistochemistry (Ihc) and Immunofluorescence (If)mentioning
confidence: 99%
“…H&E staining was used to evaluate the lung tissue from the rats. The procedure has been described in detail in the related literature [64]. The lung tissue was resected at a size of 5 μm and sectioned.…”
Section: Histological Analysis Of Rat Lungsmentioning
confidence: 99%
“…Compared with the aforementioned studies on prematurity and IUGR and their effect on glomerular vasculogenesis, research involving chorioamnionitis has focused on the postnatal effect on RAS and the subsequent development of hypertension—one of the known long-term consequences of perinatal stress. Ding et al and Hao et al showed in rodent models that chorioamnionitis increased the intrarenal expression of renin and angiotensin II in the weeks after birth without elevated levels of plasma renin activity or angiotensin II [ 68 , 69 ]. Hypertension developed simultaneously with the rise in intrarenal RAS.…”
Section: Vascular Developmentmentioning
confidence: 99%
“…Another effect of chorioamnionitis on the glomerular capillaries is the correlation between chorioamnionitis and glomerulovascular damage rendering the glomeruli increasingly susceptible for glomerulosclerosis [ 71 ]. Kidneys exposed to LPS during development show more apoptosis at birth, mainly originating from glomerular endothelial cells [ 69 ]. Guo et al showed that in adulthood, the glomeruli show increase in mesangial matrix, deposition of collagen 1 and 3 and upregulation of α-SMA in the interstitium [ 71 ].…”
Section: Vascular Developmentmentioning
confidence: 99%